Effects of Aquatic Exercise and Transcranial Direct Current Stimulation on Motor Skills and Cognitive Functions in Children with Autism Spectrum Disorder - Akbarimehr, Hanieh; Ghayour Najafabadi, Mahboubeh; Gharayagh Zandi, Hasssan; Khajavi, Daryoush (International Journal of Sport Studies for Health, 2026)
Objective: Children with autism spectrum disorder (ASD) experience distinctive neurophysiological characteristics associated with impairments in motor coordination, balance, and executive function. In recent years, aquatic exercise (hydrotherapy) and transcranial direct current stimulation (tDCS) have been introduced as promising non-invasive interventions targeting these deficits. While each approach has shown therapeutic potential when used independently, the combined effects of these interventions remain underexplored. This study aimed to examine the integrated impact of aquatic exercise and tDCS on motor performance and cognitive flexibility in children with ASD. Methods and Materials: This quasi-experimental study included 30 children aged 7–10 years diagnosed with ASD, randomly assigned to either an experimental group (aquatic exercise + tDCS; n=15) or a sham control group (n=15). The intervention lasted six weeks and comprised 18 sessions. Motor performance was assessed using the Bruininks–Oseretsky Test of Motor Proficiency (BOT-2), and cognitive flexibility was evaluated through the Wisconsin Card Sorting Test (WCST). Data were analyzed using analysis of covariance (ANCOVA) to compare pre- and post-test differences between groups. Result: The analysis revealed significant post-intervention improvements in both static and dynamic balance, as well as cognitive flexibility, in the experimental group compared with the sham group (P<0.05). These findings suggest that the combined intervention effectively enhanced both motor and executive functions in children with ASD. Conclusion: The results indicate that combining aquatic exercise with transcranial direct current stimulation can produce synergistic effects, improving balance and cognitive flexibility in children with autism spectrum disorder. This integrated, non-invasive approach may represent a valuable adjunct to conventional rehabilitation methods, though larger-scale studies with follow-up assessments are recommended to confirm long-term efficacy.